PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN ANDALIMAN (Zanthoxylum acanthopodium DC.) TERHADAP GAMBARAN MORFOLOGI OVARIUM MENCIT (Mus musculus L.) STRAIN DDW. - MELVARIANI SYARI BATUBARA; EMITA SABRI; MASITTA TANJUNG (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2017)
A study on the effect of andaliman (Zanthoxylum acanthopodium DC.) leaves ethanol extract to morphological ovary of mice (Mus musculus L.) strain DDW. has been, and was given orally by gavage on 4 days before estrus and 4 days after estrus with the volume given was 0,1 ml/10 g body weight. The research has been studied at Animal Structure And Physiology Laboratory of Department of Biology in Mathematics And Natural Science Faculty, University of  North Sumatera in Medan since February 2006 until September 2006. The research method used was completely randomized designed non factorial which consist of treatment and control groups. The treatment had one factor that is extract dosages with 2500 ppm (0,25 g/100 ml aquadest), 5000 ppm (0,5 g/100 ml aquadest), 10000 ppm (1,0 g/100 ml aquadest), 20000 ppm (2,0 g/100 ml aquadest), 40000 ppm (4,0 g/100 ml aquadest).The result showed that the chemistry consist of andaliman leaves extract is alkaloid, steroid, and saponin. The effect of andaliman leaves extract on 9 days to morphology of  ovary weight and diameter of mice did effect, but DnMRT showed non significantly effect of treatment and control groups of mice. From the result it was concluded that andaliman leaves extract did effect to ovary morphology of female mice, because can be effected oogenesis and ovulation. But the result showed that fluctuatif, because maybe the andaliman extract is crude extract that didn’t  isolation chemistry consist.